Design and semiparametric analysis of non‐inferiority trials with active and placebo control for censored time‐to‐event data. (18th March 2013) - Kombrink, Karola; Munk, Axel; Friede, Tim
<x xml:space="preserve">Abstract</x> The clinical trial design including a test treatment, an active control and a placebo is called the gold standard design. In this paper, we develop a statistical method for planning and evaluating non‐inferiority trials with gold standard design for right‐censored time‐to‐event data. We consider both lost to follow‐up and administrative censoring. We present a semiparametric approach that only assumes the proportionality of the hazard functions. In particular, we develop an algorithm for calculating the minimal total sample size and its optimal allocation to treatment groups such that a desired power can be attained for a specific parameter constellation under the alternative. For the purpose of sample size calculation, we assume the endpoints to be Weibull distributed. By means of simulations, we investigate the actual type I error rate, power and the accuracy of the calculated sample sizes. Finally, we compare our procedure with a previously proposed procedure assuming exponentially distributed event times. To illustrate our method, we consider a double‐blinded, randomized, active and placebo controlled trial in major depression. Copyright © 2013 John Wiley & Sons, Ltd.